INTERNATIONAL PROJECTS AS A WAY TO SUPPORT THE INTERNATIONALIZATION OF UNIVERSITIES - OSTENDA, Aleksander; ZASLAVSKA, Mariia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article deals with the issues of internationalization of higher educational institutions in Poland in the context of the implementation of international projects and the integration of the education sector. The directions of the country's state policy in the context of the implementation of the education reform based on new innovative ideas are considered. The level of education internationalization processes is one of the most important aspects of the country's social development. As a full member of the European Education Area, Poland automatically takes part in internationalization processes.As a result of the introduction of new innovations in the educational process, one of the topical issues has become the study of foreign experience and the introduction of international standards into the higher education system, which is of great importance for improving the quality of educational services. The mechanisms of the process of internationalization of higher education by J. Knight and M. Castells are described.Polish academic and research institutions show a growing interest in the processes of internationalization of higher education at the international, regional, national and institutional levels. Internationalization and global involvement are becoming key trends in the development of national education systems in Poland and abroad.The requirements for international assessment programs and the principles of their implementation in the Polish education system are described, as well as important features of the international assessment programs PISA, PIRLS, based on the opinions of foreign scientists, an analysis of the results of Polish students for 2021-2022 is carried out.An assessment is given to some international educational programs that are aimed at the comprehensive development of students. Examples of internal internationalization are given, which involves the creation of a university cultural climate aimed at supporting international and intercultural processes of globalization, such as participation in international educational programs or attracting foreign students and teachers.
Keywords: education system; internationalization; quality of education; PISA; PIRLS